IDENTIFIKASI NEMATODA USUS SOIL TRANSMITTED HELMINTH PADA ANAK-ANAK DI KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Dian Islamiati; Mujahidah Basarang; Muh. Rifo Rianto; Tuty Widyanti (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Soil Transmitted Helminths or intestinal nematodes are a group of intestinal worm parasites that require moist and moist soil media for their development. The soil-transmitted helminth (STH) groups are roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), hookworms (Necator americanus and Ancylostoma duodenale) and thread worms (Strongyloides stercoralis). and improper placement of waste water reservoirs results in contamination of the soil which is a breeding ground for intestinal nematodes. This study aims to identify soil-transmitted helminths in the feces of children in Baranti District, Sidenreng Rappang Regency. This type of research is laboratory observation. A total of 10 stool samples using the sedimentation method (centrifugation). Based on the results of the research that has been done, it was found that 2 samples were positive for worm eggs. Based on the results of the study, it can be concluded that soil-transmitted helminths were found in children with Ascaris lumbricoides and Trichuris trichiura eggs.